ANALYSIS BREAK EVEN POINT IN EPIC SEWING HOUSE WARD IN MOJOKERTO - Nuryadi (Sekolah tinggi ilmu ekonomi pemuda, 2022)
This study aims to describe the break even point analysis at the Epik Sewing House in Mojokerto Ward in 2017 - 2019. The data studied are sales reports of the Epik Sewing House for 2017 - 2019. The method used in this research is qualitative method. Data analysis was performed using break even point analysis, namely through the collection of data from companies such as cost data and sales data. Classify costs, calculate break even points, determine target return on capital, and make business development plans. The results show that the Break Even Point Analysis at the Epik Sewing House in Mojokerto Ward is in accordance with the calculation of the break even point in 2017, 2018, and 2019.